Uma plataforma de middleware para internet das coisas - Lavarda, Roger Luis Hoff (2018)
The advancement of wireless networks, the miniaturization and popularization of sensors and actuators and the emergence of free hardware electronic prototyping platforms, are providing a major change in how electronic devices collect and dissipate data, and consequently in the way people consume information. This new technological scenario has led to the eminent emergence of an Internet of Things. This term refers to the integration of physical and virtual objects into Internet connected networks, allowing "things" to collect, exchange, and store an enormous amount of data in a cloud. In addition to the physical devices that are part of the Internet of Things, we also need services to carry out communication between these devices and the cloud. One of the agents in Internet of Things is the middleware, an element capable of providing an abstraction of the system for applications and developers. In view of the relevance of middleware platforms for Internet of Things, as well as existing challenges and research opportunities, this work proposes the development of a middleware platform for Internet of Things, open source, with the aim of connect IoT devices, manage them, and provide data storage and visualization. The platform was developed using PHP and MySQL technologies, integrated with the Eclipse Mosquitto messaging broker. In order to evaluate the effectiveness of the platform, a case study was developed, creating communication situations in the cloud between an Android application and an Arduino device connected to the internet with WiFi Shield.